A brief history of pulse production in the Palouse region. Issue 2 (24th May 2016) - Muehlbauer, Fred; Rhoades, Drex
Abstract : Although wheat remains king of the cash crops in the Palouse, the importance of pulse crops to the region is now well established. This article looks at the history of lentil, dry pea, and chickpea production in this region as well as their existing markets. Earn 1 CEU in Crop Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/762 .